The protection of marine waters and organisms through criminal la in the legislation and practice of the Republic of Croatia - Sokanović Lucija; Mladinić Nina; Kurtović-Mišić Anita (Glasnik Advokatske komore Vojvodine)
The protection of marine waters and organisms through criminal law is primarily governed by provisions in Chapter XX of the Criminal Code, specifically concerning criminal offenses against the environment. These offenses include: Environmental Pollution (Art. 193), Discharge of Polluting Substances from a Vessel (Art. 194), Endangerment of the Environment with Waste (Art. 196, para. 2). Endangerment of the Environment with a Plant (Art. 197). Endangerment of the Environment with Radioactive Substances (Art. 198). Destruction of Protected Natural Values (Art. 200). Destruction of Habitat (Art. 201). Poaching Game and Fish (Art. 204). Killing or Torture of Animals (Art. 205). Transmission of Contagious Animal Diseases and of Organisms Harmful to Plants (Art. 206). The listed criminal offenses are based on contemporary biocentric concepts of the object of protection. The legal framework for the protection of marine waters and organisms through criminal law is based on the definition of the marine environment provided in the current Environmental Protection Act. Following the introduction, the paper outlines the general characteristics of the protection of the environment through criminal law, with a specific focus on marine waters and organisms, as well as the concept of maritime environmental crime. It further identifies criminal offenses against the sea and marine environment and examines their alignment with relevant European Union regulations. A significant portion of the paper is dedicated to analyzing the practice of state attorneys and courts in this context.